Differential Effects of Components in Artemisia annua Extract on the Induction of Drug-Metabolizing Enzyme Expression Mediated by Nuclear Receptors - Zhang, Xueli; Meng, Ran; Wang, Haina; Xing, Jie (Planta Medica, 2020)
Artemisia annua tea is a popular dosage form used to treat and prevent malaria in some developing countries. However, repeated drinking leads to an obviously decreased efficacy, which may be related to the induction of metabolizing enzymes by artemisinin. In the present study, the ability of different components in A. annua to activate the pregnane X receptor and constitutive androstane receptor was evaluated by the dual luciferase reporter gene system. The changes in mRNA and protein expression of CYP3A4 and CYP2B6 were determined by quantitative real-time PCR and Western blotting. Results showed that in the pregnane X receptor-mediated CYP3A4 reporter gene system, chrysosplenetin and arteannuin B exhibited a weak induction effect on pregnane X receptor wt, while arteannuin A had a strong induction effect on pregnane X receptor wt and pregnane X receptor 370 and a weak induction effect on pregnane X receptor 163. In the pregnane X receptor-mediated CYP2B6 reporter gene system, arteannuin A had a moderate induction effect on pregnane X receptor wt and pregnane X receptor 379, and a weak induction effect on pregnane X receptor 403, while arteannuin B had a weak induction effect on pregnane X receptor wt and pregnane X receptor 379. Arteannuin A had a strong induction effect on constitutive androstane receptor 3 in constitutive androstane receptor-mediated CYP3A4/2B6 reporter gene systems, while arteannuin B showed a weak induction effect on constitutive androstane receptor 3 in the constitutive androstane receptor-mediated CYP2B6 reporter gene system. The mRNA and protein expressions of CYP3A4 and CYP2B6 were increased when the pregnane X receptor or constitutive androstane receptor was activated. Various components present in A. annua differentially affect the activities of pregnane X receptor isoforms and the constitutive androstane receptor, which indicates the possibility of a drug-drug interaction. This partly explains the decline in efficacy after repeated drinking of A. annua tea.
Keywords: arteannuin A; arteannuin B; Artemisia annua; Asteraceae; metabolic drug-drug interactions; CYP3A4/2B6; PXR/CAR